STRATEGI PEMBELAJARAN MUSIK ENSEMBLE MELALUI MEDIA GAMELAN DEGUNG PADA SISWA KELAS V SEKOLAH DASAR - Subandi, Didi; Julia, Julia; Gusrayani, Diah (Jurnal Pena Ilmiah, 2017)
The purposes of this observation is to describe the process, result, learning evaluation of ensemble music using gamelan degung media. This observation is a descriptive method observation using twelve fifth grade students from SDN Ambit Situraja Subdistric, Sumedang District. This observation using Miles Huberman model for data processing consist of data reduction, display data and conclution drawing/verification. The used instruments are observation sheets, interview and documentation guidance. The learning process of ensemble music using gamelan degung consists of several steps; (a) listening of ensemble music theory including of ensemble music performance using gamelan degung. (b) Gamelan degung instruments introduction. (c) motivating step to persuade the students to make them interest to play gamelan degung ensemble music. (d) teaching the playing techniques to play gamelan degung through how to hold and play the gamelan instruments. (e) giving simple music notation such as â€œGambir Sawitâ€ song to be learnt and played using gamelan degung. (f) doing intensive rehearsalÂ  to play the song. (g) giving a result evaluation for the ensemble music lesson. The result of ensemble music learning using gamelan degung is the students skill to play gamelan degung as Nusantara culture. Aligned with the purposes of art education to conserve andÂ  bequeath art to young generation. Learning ensemble music using gamelan degungâ€™s evaluation held on simple performance using three assessment criteria, rote the songÂ  (cognitive), gamelan degung playing technique (psychomotor) and attitude at the time of playing the gamelan degung (affective).